Pengaruh service quality dan reference group terhadap keputusan konsumen dalam berbelanja di Lotte Mart - Kurniawan, Ryan; Matahari, Riki (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research is motivated by the growth rate of hypermarkets in Bandung. This of course will affect the number of people who shop in modern markets or hypermarkets. Shopping service providers must prepare the best strategy to attract consumers, because with the emergence of new outlets, consumers have more choices. Lotte Mart hypermarket is one of the outlets affected by this imbalance. It can be seen from the number of outlets between its competitors, namely Indomart. The problem in this study is